Pengaruh Kadar Lumpur Material Terhadap Kuat Tekan Beton Pada PC Spun Pile Di PT Jaya Beton Indonesia Surabaya - Al Abror, Izza Muhajjir (Universitas Negeri Surabaya, 2023)
The quality of concrete is declared high if it is able to withstand the force load exerted during high compressive strength tests, one of which is the quality of fine aggregates to be used in making concrete. This study aims to determine the influence of the substances contained or the level of sludge present on fine aggregates. The research method was carried out by taking laboratory testing data on sludge content by testing slump and compressive strength of concrete samples aged 28 days cylindrical with a diameter of 10 cm and a height of 20 cm with 5 variations of fine aggregate sludge content of 1.5%, 1.7%, 2.4%, 2.7%, 3.6% with a planned f'c of 50 Mpa. The results of slump test testing studies on variations in sludge content of 1.5%, 1.7%, 2.4%, 2.7%, and 3.6% have different slump values, the higher the sludge content, the higher the slump value or the thinner the concrete mixture. The mud content of 1.5% has a slump value of 5.5 cm while the mud content of 3.6% has a slump value of 7.5 cm. The compressive strength results on the test specimen at the age of 28 days, the higher the mud content, the decrease in compressive strength and quality values. At 1.5% mud content produced an average compressive strength of 494.3 kN and an average concrete quality of 62.972 Mpa, while at 3.6% mud content produced an average compressive strength of 414 kN and an average concrete quality of 52.738 Mpa.